1957
DOI: 10.1161/01.res.5.1.91
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Intercoronary Reflexes

Abstract: There is no evidence in the anesthetized dog that occlusion of one of the three coronary arteries leads to vasoconstriction in the vascular areas irrigated by the other two arteries. On the contrary, occlusion of one coronary artery appears to lead to a decrease in the resistance of the two adjacent vascular beds in most experiments. The mechanisms and the implications of this effect are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1958
1958
1980
1980

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…1 and 2). Although it has been suggested that reflex coronary constriction results from occlusion of adjacent coronary arteries (14), the increase in arterial inflow in the nonoccluded artery in the present experiments is in agreement with the studies reported by most other investigators who found that coronary resistance predominantly decreases in adjacent, nonoccluded vessel (1)(2)(3)(4)(5)(6). The observed decrease in O2 content and increase in flow in the great cardiac vein do not support the concept of reflex dilatation of the left anterior descending artery which it drains.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 and 2). Although it has been suggested that reflex coronary constriction results from occlusion of adjacent coronary arteries (14), the increase in arterial inflow in the nonoccluded artery in the present experiments is in agreement with the studies reported by most other investigators who found that coronary resistance predominantly decreases in adjacent, nonoccluded vessel (1)(2)(3)(4)(5)(6). The observed decrease in O2 content and increase in flow in the great cardiac vein do not support the concept of reflex dilatation of the left anterior descending artery which it drains.…”
Section: Discussionsupporting
confidence: 93%
“…ADDITIONAL KEY WORDS coronary reflex myocardial pressure cardiac metabolism anesthetized dogs venous oxygen collateral circulation • Several investigators have reported that occlusion of a major branch of a coronary artery results in an increased flow in adjacent coronary arteries (1)(2)(3)(4)(5)(6). The mechanism of this response is not known.…”
mentioning
confidence: 99%
“…It has been frequently reported that occlusion of a major branch of the canine left coronary artery results in an increased blood flow through the remaining arteries (21)(22)(23)(24)(25)(26). Venous outflow from the great cardiac vein is increased after ligation of the left anterior descending coronary artery, whereas oxygen saturation of venous blood from nonischemic muscle declines (26).…”
Section: Discussionmentioning
confidence: 99%
“…This is usually attributed to a vasoconstrictor reflex which may be blocked in various ways. However, most recent reports have demonstrated an increase in flow in vessels adjacent to an occluded artery (4)(5)(6)(7)(8)(9)(10)(11)(12). These studies range from acute experiments on anesthetized animals subjected to major surgery to elegant chronic studies of conscious, trained animals with gradually induced coronary obstruction (15).…”
Section: Rees Reddingmentioning
confidence: 99%
“…Some previous studies indicated a reduction in flow, but more often an increase was found, particularly when blood pressure was kept constant. When pressure was allowed to change, flow elsewhere in the heart was usually reduced or unaltered (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%